2019
DOI: 10.3390/genes10100743
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Transcriptomic Analysis Reveals Distorted Ion Homeostasis and Responses in the Freshwater Plant Spirodela polyrhiza L. under Salt Stress

Abstract: Duckweeds are a family of freshwater angiosperms with morphology reduced to fronds and propagation by vegetative budding. Unlike other angiosperm plants such as Arabidopsis and rice that have physical barriers between their photosynthetic organs and soils, the photosynthetic organs of duckweeds face directly to their nutrient suppliers (waters), therefore, their responses to salinity may be distinct. In this research, we found that the duckweed Spirodela polyrhiza L. accumulated high content of sodium and redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 97 publications
0
16
0
Order By: Relevance
“…In the study performed by Fu et al (2019) using S. polyrhiza 7498, it was reported that in the first few hours of treatment until 12 h, the starch content decreased and this correlated positively with the activity of AGP, the initial and rate-limiting enzyme of starch synthesis, which is involved in starch biosynthesis. A set of transcriptomic data with differentially expressing gene patterns, related to the time points within a day of treatment have also been presented.…”
Section: Salt Stress On Starch Accumulationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study performed by Fu et al (2019) using S. polyrhiza 7498, it was reported that in the first few hours of treatment until 12 h, the starch content decreased and this correlated positively with the activity of AGP, the initial and rate-limiting enzyme of starch synthesis, which is involved in starch biosynthesis. A set of transcriptomic data with differentially expressing gene patterns, related to the time points within a day of treatment have also been presented.…”
Section: Salt Stress On Starch Accumulationmentioning
confidence: 99%
“…and Ca 2? content (Fu et al 2019). Of interest is the increase of ABA levels by 150% with the treatment of duckweeds with 85 mM NaCl (Huber and Sankhla 1979) as it is known that ABA induces, very effectively, starch accumulation in duckweeds.…”
Section: Salt Stress On Starch Accumulationmentioning
confidence: 99%
“…This is particularly evident in land plants as JAs can alleviate salt stress by increasing the endogenous hormones and the antioxidative system [ 57 , 58 , 59 , 60 ]. Downregulation of three LOXs has been shown in a previous transcriptome analysis of duckweed exposed to salt stress [ 61 ]. However, our studies demonstrated that salt stress of duckweeds causes a dynamic pattern of the LOX gene family, with induction of several of them within 6 h of salt exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Relative gene expression was quantified according to the 2 −∆∆ C T method [ 73 ]. The S. polyrhiza actin (Spipo17G0011400) and 18S rRNA (Spipo23G0000600) genes were used as standard housekeeping genes to normalize the expression of target genes [ 61 ]. qRT-PCR data represent the average ± standard deviation from a minimum of three independent biological replicates for each gene.…”
Section: Methodsmentioning
confidence: 99%
“…The temporal and spatial expression pro les of SpGARPs in different tissues/organs (leaves, roots, and stipule, Bio-Project PRJNA557001), under various nutrient stresses (supply with P and N (+ P/+N), N deprivation (+ P/−N), P deprivation (− P/+N), P and N deprivation (− P/−N), and none nutrient supply (H 2 O) for seven days, PRJNA724886), under salt stress (salt-0 h, salt-6 h, salt-12 h, salt-24 h, PRJNA563960) were obtained using the publicly available transcriptome data from NCBI [23,73]. The heat map showing the correlations between the expression patterns of SpGARP genes was generated with the gplots package in R (version 4.1.2, https://www.R-project.org/).…”
Section: Rna-seq Atlas Analysismentioning
confidence: 99%